Awareness and compliance with tobacco control policies among retailers near schools in Arghakhanchi, Nepal: A mixed- methods study. - Arjun Poudel; Hari Prasad Kaphle; Sunita Poudel; Sagar Parajuli; Kumud Bhurtel; Shalik Ram Dhital (PLOS Global Public Health)
Tobacco consumption is the second leading cause of death among adults, and it is a major public health challenge worldwide including Nepal. This paper aims to assess awareness and compliance of tobacco legislation among retailers located nearby schools, and facilitators, and barriers to the implementation of legislation at the district level. A cross-sectional mixed-methods study design was carried out among randomly selected retailers (n = 203) located within 100 meters of schools from 51 sites, along with 8 Key Informant Interviews (KII) with purposefully selected implementation-level officials. Data were collected using an interview schedule, a checklist, and KII guideline. Awareness and compliance of retailers were measured for 14 provisions of the Tobacco Products (Control and Regulatory) Act (TPCRA), 2011 of Nepal. Bivariate and multivariate analyses were conducted to identify associations between dependent variables and independent predictors for policy compliance, and manual thematic analysis was performed for qualitative data. Only one third (33%) of retailers were found aware on provisions of TPCRA while majority (93.6%) of retailers were found violating policy provision by selling tobacco close to school. Only 14.7% of retailers were found in compliance with provision of not selling tobacco to minors and 5.8% retailers were found restricting sale of loose cigarettes. Retailers of rural settings were found two times (aOR 2.50, 95% CI, 0.99-6.27) more likely to comply with banning to tobacco sale to minors as compared to urban retailers. The enforcement of legislation, dedicated inspection mechanism and raised public awareness were found as key facilitators for policy implementation. Awareness and compliance among retailers were found to be inadequate despite the enforcement of the TPCRA since 2011. In order to strengthen policy implementation, it is essential to raise awareness, conduct regular and rigorous market inspection, and empower officials and elected representatives to take proactive measures.